Pengembangan Inisiatif, Kemandirian, dan Tanggung Jawab untuk Meningkatkan Kualitas Pembelajaran Peserta Didik - Suherman Suherman; Amin Budiamin (Indonesian Journal of Educational Counseling, 2020)
DEVELOPMENT OF INITIATIVES, INDEPENDENCE, AND RESPONSIBILITIES FOR IMPROVING THE QUALITY OF STUDENT LEARNING. The learning process will take place effectively and productively if students have psychological competence and strength in the form of initiative, independence, and responsibility in learning activities. Students who have the initiative, independence, and low responsibility are suspected to experience obstacles and difficulties in the learning process, and will be trapped in immaturity and stagnation in development. This research aims to develop guidelines for the development of initiatives, independence, and responsibility, so that students can undergo the learning process effectively and independently. If students have the initiative, independence, and responsibility, the learning process is expected to produce quality outputs that can develop students to have abilities according to their potential, can face future challenges, and have quality job and career orientation, so they are able to compete in a global society. With a quasi-experimental method and collaborative action research approach, this study involved 260 respondents and two guidance and counseling teachers in two state junior high schools in West Bandung Regency. The research produced guidelines that were tested that could effectively develop the initiative, independence, and responsibility of junior high school students.